A study of early versus conventional oral feeding in women undergoing caesarean section - Nagraj, Devina; Yi, Ching Ling; Dalal, Asha R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Traditionally women undergoing lower segment caesarean section (LSCS) had oral food withheld for12-24 hours to prevent gastrointestinal complications. However, it was observed in many studies, that early oral feeding to patients post LSCS improves recovery and decreases chances of post-operative complications. Methods: This was a randomized interventional study conducted in a public hospital. Uncomplicated patients who underwent LSCS under regional anesthesia were selected. Group A and B with 100 participants each were made. One group (A) was given early orals (6 hours) and other group (B) was given orals after 12 hours. Results: The early feeding group had earlier return of bowel movements and earlier passage of flatus (8 and 13 hours) as opposed to delayed feeding group (10 and 18 hours). 13% patients in the early feeding group had complications as opposed to 43% patients in the delayed feeding group. The most common complication was abdominal distension which was seen in 5 and 10 patients of the early and delayed feeding group respectively. Conclusions: Early oral feeding after LSCS can lead to early recovery, better mother and child health, better utilization of the hospital resources and decreased financial burden on the family as well as the government in the long run.